A 30‐Year Clinical and Magnetic Resonance Imaging Observational Study of Multiple Sclerosis and Clinically Isolated Syndromes - Chung, Karen K.; Altmann, Daniel; Barkhof, Frederik; Miszkiel, Katherine; Brex, Peter A.; O'Riordan, Jonathan; Ebner, Michael; Prados, Ferran; Cardoso, M. Jorge; Vercauteren, Tom; Ourselin, Sebastien; Thompson, Alan; et al. (Annals of neurology, 2020)
Objective Clinical outcomes in multiple sclerosis (MS) are highly variable. We aim to determine the long‐term clinical outcomes in MS, and to identify early prognostic features of these outcomes. Methods One hundred thirty‐two people presenting with a clinically isolated syndrome were prospectively recruited between 1984 and 1987, and followed up clinically and radiologically 1, 5, 10, 14, 20, and now 30 years later. All available notes and magnetic resonance imaging scans were reviewed, and MS was defined according to the 2010 McDonald criteria. Results Clinical outcome data were obtained in 120 participants at 30 years. Eighty were known to have developed MS by 30 years. Expanded Disability Status Scale (EDSS) scores were available in 107 participants, of whom 77 had MS; 32 (42%) remained fully ambulatory (EDSS scores ≤3.5), all of whom had relapsing–remitting MS (RRMS), 3 (4%) had RRMS and EDSS scores >3.5, 26 (34%) had secondary progressive MS (all had EDSS scores >3.5), and MS contributed to death in 16 (20%). Of those with MS, 11 received disease‐modifying therapy. The strongest early predictors (within 5 years of presentation) of secondary progressive MS at 30 years were presence of baseline infratentorial lesions and deep white matter lesions at 1 year. Interpretation Thirty years after onset, in a largely untreated cohort, there was a divergence of MS outcomes; some people accrued substantial disability early on, whereas others ran a more favorable long‐term course. These outcomes could, in part, be predicted by radiological findings from within 1 year of first presentation. ANN NEUROL 2020;87:63–74